A preliminary study on the relationship between handwriting pressure and pressure exerted during cavity preparation - Barles, Emmanuel V.
This paper is a preliminary study conducted to determine if there is relationship between handwriting pressure and pressure exerted during cavity preparation. A group of thirty third year 2nd semester students of the UPCD were randomly selected. Subjects were asked to perform handwriting exercises and box cavity preparations on mounted teeth. Analysis of the results show that there is a significant correlation between handwriting pressure and pressure exerted during cavity preparation.